The Methodology Of Organizing Classes In Applique And Mosaic For Elementary School Students - Yuldasheva Yulduz Zhovlievna (Genius Publishing Group, 2024)
The article provides information that the practice of application in technology lessons is of great importance for the harmonious development of students and that application greatly helps in the development of creativity and enriches the imagination, activates observation and attention, educates the will, develops guessing, as well as color perception.
Keywords: applique; decorative; plot